IFRS and Stock Returns: An Empirical Analysis in Brazil - Malaquias, Rodrigo F.; Cardoso, Anderson Martins; Martins, Gabriel Alves (Binus Business Review, 2016)
In recent years, the convergence of accounting standards has been an issue that motivated new studies in the accounting field. It is expected that the convergence provides users, especially external users of accounting information, with comparable reports among different economies. Considering this scenario, this article was developed in order to compare the effect of accounting numbers on the stock market before and after the accounting convergence in Brazil. The sample of the study involved Brazilian listed companies at BM&FBOVESPA that had American Depository Receipts (levels II and III) at the New York Stock Exchange (NYSE). For data analysis, descriptive statistics and graphic analysis were employed in order to analyze the behavior of stock returns around the publication dates. The main results indicate that the stock market reacts to the accounting reports. Therefore, the accounting numbers contain relevant information for the decision making of investors in the stock market. Moreover, it is observed that after the accounting convergence, the stock returns of the companies seem to present lower volatility.